Infants Born to Mothers With a New Coronavirus (COVID-19) - Chen, Yan; Peng, Hua; Wang, Lin; Zhao, Yin; Zeng, Lingkong; Gao, Hui; Liu, Yalan (Frontiers in Pediatrics, 2020)
A novel viral respiratory disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for an epidemic of coronavirus disease 2019 (COVID-19) in China and cases worldwide. Four full-term, singleton infants were born to pregnant women who tested positive for COVID-19 in the city of Wuhan, capital of Hubei province, China, where the disease was first identified. Of the three infants who were consented to be diagnostically tested, none tested positive for the virus. None of the infants developed serious clinical symptoms such as fever, cough, diarrhea, or abnormal radiologic or hematologic evidence, and all four infants were alive at hospital discharge. Two infants had rashes of unknown etiology at birth, and one had facial ulcerations. One infant had tachypnea and was supported by non-invasive mechanical ventilation for three days. One had rashes at birth but was discharged without parental consent for a diagnostic test. This case series describes the report to describe the clinical course of 4 live born infants born to pregnant women with COVID-19 infection.